Juvenile Justice Paradigms and Improvement of Realization of the Constitutional Rights and Freedoms of Man and Citizen in Russia - M. R. Arpentieva (Сибирское юридическое обозрение, 2015)
The article is devoted to the problems of implementation and procedures of reconstructing model of juvenile justice system, it considers foreign and domestic experience (problems) of juvenile justice. The author compares the doctrines of juvenile justice, including the doctrine of punitive and understanding justice.